Catalan nationalism : Francoism, transition and democracy - Guibernau i Berdún, M. Montserrat (Maria Montserrat) (Routledge/Cañada Blanch studies on contemporary Spain, 2004)
Catalan Nationalism offers a fresh socio-political analysis of Catalan nationalism during the Franco regime (1939-1975) and the Spanish transition to democracy.